Building productivism in rural China: The case of residential restructuring in Chengdu - ZHANG, Qian Forrest (Institutional Knowledge at Singapore Management University, 2022)
This paper theorizes the rural restructuring in China today as a transition towards productivism – characterized by both a productivist agricultural regime and productivist rural spaces. The rise of the productivist agricultural regime has spearheaded this transition for two decades; now the residential restructuring programs implemented under various policy schemes are also producing spaces of productivism in the new concentrated settlements. This paper, employing Halfacree’s three-fold conceptual model of rural space and using the empirical case of residential restructuring in Chengdu, offers the first full analysis of the rise of productivism in all three facets of rural space. It demonstrates both how formal representations and planning practices are building spaces of productivism in a multi-scalar process and how this new spatiality is contested and modified by residents in their everyday lives, creating tensions and contradictions in the emerging productivist rural spatial regime. A key insight from this study is that the productivist transformation of residential space is constitutive of the broader transition to productivism and crucial to the rise of productivist agriculture.